Index Informativeness: An Empirical Study on Indonesia Stock Exchange - Heriyanto, Heriyanto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This study aims to determine the market's reaction to the announcement of company list change’s at LQ45 Index, Jakarta Islamic Index (JII), and SRI-KEHATI Index. Sample of this research is company stocks that include in or exclude from LQ45 Index, JII, and SRI-KEHATI Index during the period 2009 to 2018. The results showed that in general in the sample group of companies included in the Index, no significant market reaction was found. For the sample group of companies excluded from the Index, significant negative market reactions were found from all the Index. Furthermore, there was no significant difference in market reaction was found, both in the sample group included and in the sample group excluded from the Index. Significant different market reaction were only found in the LQ45 Index and JII.